The First Annual South El Monte High School Environmental Awareness/ Career Day - National Hispanic Environmental Council (National Hispanic Environmental Council)
A collaborated program between National Hispanic Environmental Council and South El Monte High School with the purpose of educating and train minority high school and college students in an array of environmental fields. This is a flier to announce the first annual environmental awareness/ career day with information on specifics.